Economic Effects of VAT Reform in Germany - Stefan Boeters; Christoph Böhringer; Thiess Büttner; Margit Kraus (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2006)
In the tax policy debate, differentiation of value-added taxes is often justified by distributional concerns. Our quantitative analysis for Germany indicates that such concerns are misplaced. We find that the abolition of VAT differentiation has only negligible redistributive effects. Instead, reduced VAT are found to act as industry-specific subsidies. Whereas the overall welfare effects of pure VAT reforms are very small, a revenue-neutral introduction of a harmonised VAT combined with reductions in the marginal income tax rates or social security contributions turns out to produce substantial welfare gains for all households.
Keywords: H24; H22; D58; 330; VAT; tax reforms; distribution; efficiency; applied general equilibrium; Umsatzsteuer; Steuerbegünstigung; Steuerinzidenz; Steuerwirkung; Wohlfahrtseffekt; Steuerreform; Allgemeines Gleichgewicht; Deutschland